Оptimization of power control program switching for a WWER-1000 under transient operating conditions - Huiyu Zhou; Pelykh, S.N.; Odrekhovska, I.O.; Maksymova, O.B. (Вопросы атомной науки и техники, 2018)
This paper is devoted to solution of the scientific and technical problem of safe switching of static power control programs for a nuclear power unit with a WWER-1000 under transient operating conditions, so that to minimize the influence of disturbances of external and internal operating parameters, as well as to increase the safety and efficiency of reactor operation. The switching optimization task for static power control programs has been solved by finding a decision of the objective function which allows to switch safely the energy equipment modes in a predetermined range of load variations. The possibility of switching between static power control programs during a 4-year reactor campaign has been studied. The control program optimization problem for anuclear power unit with a WWER-1000 operated under variable loading, considering different power control programs during a 4-year campaign, has been solved.